PENAKSIR RASIO DAN PRODUK EKSPONENSIAL YANG EFISIEN UNTUK RATA-RATA POPULASI PADA SAMPLING ACAK SISTEMATIK - Fanny Wirastuti; Bustami '; Haposan Sirait (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
The estimators discussed in this paper are the ratio exponential estimator, the product exponential estimator and the combination of ratio exponential estimator and product exponential estimator on systematic random sampling, which is a review and an expansion correction from the article of Singh, et. al. [Journal of Modern Applied Statistical Methods, 10: 424-435]. Each estimator is a biased estimator and the mean square errors are determined. Estimator with the smallest mean square error is the most efficient estimator. An example is given at the end of the discussion.